(3QSGdI aj GdcjejGAs - (3CMeO Hf GjhH GdUfgGLjs
(3ChdgG (B:s
(3CYde jG CNj habc Gddg hGjGfG Edi SHjd GdNjQGJ Cf CjSQ GdPi CcKQhG ajg GdadGSaI GdeGVjjf Gdbhd EfeG gh MLQ eKdK GdcJGHf eQJY GdcjajI bO LeY GdWHGFY cdgG aef CLd Pdc cKQJ CSeGDg s
(3BNQgG (B:s
(3bGd GdMcje NP ef GdCShO KdGKI CLQGA hef GdeGA GdNGdO LRA hGMO hGYbOgG ceG JYQa JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs